Case study of children of referrals to health services: an individualizing design? - Rondini, Carina Alexandra [UNESP]; Incau, Camila; Reis-Yamauti, Verônica Lima dos (Scientific Research Publishing, 2015)
Nowadays education for all is recommended as an international action. However in Brazil one can observe homogeneous practices for a heterogeneous public. When the student has learning difficulties, there seems to be an attempt to normalization and pathologization by the means of referral, many times being indiscriminate, to health services. This case study aimed to analyze records of pedagogical strategies to meet the students educational needs before sending them to health services. Two records sent to a multidisciplinary team of a Regional Specialty Clinic (ARE) in a city of the state of São Paulo/Brazil, were used. The results reflect that the records of the educators do not show the pedagogical strategies used with the students and that the education system still seeks homogeneous classes, devaluating the diversity present in its context.
Keywords: Pathological; Diversity; Learning Problems; Health Services